Do teachers' educational philosophies affect their digital literacy? The mediating effect of resistance to change - Alanoglu, Muslim; Aslan, Serkan; Karabatak, Songul (Springer, 2022)
This study aims to reveal the direct and indirect effects of primary school teachers' educational philosophies on their digital literacy through resistance to change. A cross-sectional research design was used in the current study. Data were collected from 298 primary school teachers working at primary schools located in a city centre in the Mediterranean region of Turkey. The relationships between the variables were tested through the use of the structural equation model. The study results indicated that the teachers' traditional and contemporary educational philosophies did not directly affect their digital literacy levels, but indirectly affected their resistance to change through the level of resistance to change. The results also suggested that teachers' traditional educational philosophies had a negative effect on their digital literacy levels through the mediating role of resistance to change, while the contemporary educational philosophies positively affected their digital literacy levels through resistance to change. Consequently, in recent conditions teachers are expected to develop both their own and students' digital skills. Due to the importance of digital literacy in this age where technology permeates every aspect of life, teachers should accept digital change and transformation without resistance.
Keywords: Educational philosophy; Digital literacy; Resistance to change; Teacher; Digital age